THE ROLE OF THE MUSIC TEACHER IN THE PROCESS OF EDUCATIONAL MORAL FEELINGS OF CHILDREN - P. Yodosheva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Musical education has a significant impact on the moral and aesthetic development of the child’s personality. Educating moral feelings, we are laying the groundwork for the formation of hisher moral consciousness, the regulation of ethical behavior in the future. Therapeutic effect of music is considered, music and musical activity are regarded as means of emotional adjustment.